2016
DOI: 10.1007/s00284-016-1182-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cinnamoyl Esterases from Different Lactobacilli and Bifidobacteria

Abstract: A high variety of plants that are used for food production contain esterified hydroxycinnamic acids. As their free forms display several benefits, like an enhanced absorption in human intestinal tract, anti-oxidative and anti-carcinogenic effects, an improved protein solubility and reduced discoloration, the microbial ability to cleave the ester bond is highly desired. In order to examine potential fermentation strains for this purpose, six different lactic acid bacteria and one bifidobacterial strain were scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 46 publications
5
35
1
Order By: Relevance
“…Surprisingly, the optimal pH of these four esterase activities ranged from 7.0 to 8.0, although these enzyme-producing strains were isolated from acidic niches ( Figure 5C ). This finding was also found with other Lactobacillus FAEs (Sawatari and Yokota, 2007; Fritsch et al, 2017). In order to clarify why the optimal pH of Lactobacillus -derived FAEs was slightly alkaline, we examined the intracellular and extracellular FAE activities of L. amylovorus CGMCC 11056.…”
Section: Discussionsupporting
confidence: 84%
“…Surprisingly, the optimal pH of these four esterase activities ranged from 7.0 to 8.0, although these enzyme-producing strains were isolated from acidic niches ( Figure 5C ). This finding was also found with other Lactobacillus FAEs (Sawatari and Yokota, 2007; Fritsch et al, 2017). In order to clarify why the optimal pH of Lactobacillus -derived FAEs was slightly alkaline, we examined the intracellular and extracellular FAE activities of L. amylovorus CGMCC 11056.…”
Section: Discussionsupporting
confidence: 84%
“…Therefore, this study infers that the Methanobrevibacter genus can affect the pathway of energy metabolism, and increasing fat can reduce methane production within a certain range. Dialister genus within the phylum Firmicutes was related to lipid and glucose metabolism, glucose tolerance and the inflammatory immune responses [57,58]. This was similar to our experimental predictions.…”
Section: Discussionsupporting
confidence: 84%
“…These enzymes have been largely described in Lactobacillus and Bifidobacterium spp. [167][168][169][170][171]. Concerning Weissella spp., only a few studies reported these activities.…”
Section: Role In Bioavailability and Antioxidant Activitiesmentioning
confidence: 99%